2020
DOI: 10.2494/photopolymer.33.583
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pressure-induced Variations in the Crystalline Structures of Polyimides Having Flexible Linkages by Wide-Angle X-ray Diffraction

Abstract: Pressure-induced variations in the crystalline structures of polyimides (PIs) that have flexible ether or thioether linkages along the main chain were analyzed by synchrotron wideangle X-ray diffraction at high pressures up to 2.0 GPa. The crystalline lattices of poly(4,4oxidiphenylene pyromellitimide) (PMDA/ODA) and poly(4,4'-diamino-diphenyl sulfide pyromellitimide) (PMDA/SDA) PIs that have one flexible linkage in their repeating unit showed negative linear compressibility along the main-chain direction (c-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Takizawa, Wakita, and Ando et al [15,[19][20][21] measured wide-angle X-ray diffraction (WAXD) patterns of fully aromatic and semialiphatic PIs under high pressures up to 8 GPa. For the sBPDA/PPD PI, the d(004) spacing along the c-axis was slightly decreased due to shrinkage of the bond lengths under high pressure (figure is not shown) [19], whereas the d(002) spacing of PMDA/ODA surprisingly increased at pressures up to 0.4 GPa, which originated from bond angle changes at the ether groups.…”
Section: Spectroscopic Changes In Polyimides Induced By Ultrahigh Pre...mentioning
confidence: 99%
“…Takizawa, Wakita, and Ando et al [15,[19][20][21] measured wide-angle X-ray diffraction (WAXD) patterns of fully aromatic and semialiphatic PIs under high pressures up to 8 GPa. For the sBPDA/PPD PI, the d(004) spacing along the c-axis was slightly decreased due to shrinkage of the bond lengths under high pressure (figure is not shown) [19], whereas the d(002) spacing of PMDA/ODA surprisingly increased at pressures up to 0.4 GPa, which originated from bond angle changes at the ether groups.…”
Section: Spectroscopic Changes In Polyimides Induced By Ultrahigh Pre...mentioning
confidence: 99%
“…Investigating the relationships between the thermal expansion behaviors of the crystalline lattice and the molecular aggregation structures clarified that the coefficients of volumetric thermal expansion (CVEs) of the crystallites are negatively and linearly correlated with the weight density of the crystalline lattice . Pressure is a more ideal and effective mechanism than temperature for perturbing the molecular aggregation structures because the interchain distances of PI chains in the crystal lattice can change owing to the compression of free volume and conformational changes in the main chains. Ito clarified that the isothermal compressibility of the crystalline lattice (β 0 ) of commodity polymers, such as polyethylene, and engineering polymers, such as nylon-6, decreases with an increase in the lattice packing density. In addition, we reported that the volumetric compressibility of the crystalline lattices of PIs up to 8 GPa is dependent on the primary structures, in which the lattice compression is enhanced with an increase in the conformational freedom.…”
Section: Introductionmentioning
confidence: 99%